Identité(s) en interaction - Des adolescents déficients auditifs en classe d’intégration - Groeber, Simone (Travaux neuchâtelois de linguistique, 2012)
The aim of this paper is to investigate the interactional management of identity of three hearing-impaired pupils in a regular hearing classroom. Drawing on Conversation Analysis, we study identity in a dynamic interactive perspective by focusing on the interactional organization by means of which membership to categories is claimed and interactively co-constructed. The analysis of 11 videorecorded lessons suggests that the pupils’ ways of participating in teacher-fronted activities display their orientation to specific identities, which can be seen as part of their socialization into the hearing classroom community. It further endorses the understanding of identity work as a resource for accomplishing interactional tasks that become relevant in the jointly managed courses of actions.